Characterization of Silver Nanoparticles Prepared in the form of Powder and Their Application on Filters and Their Efficiency in Removing Bacteria Contaminating Drinking Water - Ali Khadhir, Sabah; Habeeb, Ammar A.; Abd, Muhannad Mahdi (Indonesian Journal of Material Research, 2024)
In order to ensure the availability of pure water free from contaminants, we focused on developing different laboratory-made filters and applying the ready-made nanosilver type Ag1 and the prepared type Ag2 prepared in the laboratory and loading them on the filters. We evaluated their effectiveness in removing and inhibiting bacteria based on the filter type and pore size, and we observed an increase in inhibition efficiency. In addition, we subjected the samples to UV testing within the wavelength range of 200-800, which is the range of nanosilver. We used EDX to confirm the presence of nanosilver in the samples. AFM examination, which shows the surface roughness values, pressure and grain size distribution of the prepared particles, and SEM examination, which shows the particle distribution, shapes and size measurement. To verify the stability of Nano silver and its strong negativity and confirm its size, a Zet test was performed to determine the negativity of the material and the nano size. The resulting water was analyzed with a TDS device to measure the dissolved salts in the water resulting from the different manufactured filters and to evaluate the drinking water and ensure that it is within acceptable levels. Then we used the Atomic Assay (AAS) to measure the percentage of nano silver in the drinking water resulting from the prepared filters and that the silver present does not affect the water because its percentage is very small and the silver loaded on the different filters has a moderate toxicity percentage that does not affect the water.